Impact of Venous Thromboembolism on Readmissions and Resource Use Following Emergency General Surgery. Issue 10 (October 2022) - Dobaria BS, Vishal; Hadaya, Joseph; Ebrihiminan, Shayan; Verma, Arjun; Sanaiha, Yas; Benharash, Peyman
Background: Acute deep vein thrombosis and pulmonary embolism collectively known as venous thromboembolism (VTE), are associated with increased risk of poor clinical sequelae during inpatient hospitalizations. We examined the association of VTE with mortality, readmissions, and costs among patients undergoing emergency general surgery (EGS) operations using a national cohort. Methods: Adult hospitalizations for EGS (laparotomy, small bowel resection, large bowel resection, appendectomy, lysis of adhesions, cholecystectomy, and repair of perforated ulcer) within two days of admission were identified in the 2016-18 Nationwide Readmissions Database. Hospitalizations were stratified based on diagnosis of VTE and others (n-VTE). Results: Of an estimated 860, 747 EGS patients 7, 513, (.87%) developed VTE during the index hospitalization. Patients in the VTE group were on average older (65.5 ± 15.3 vs 54.8 ± 18.6 years, P < .001) and more commonly male (46.7 vs 39.3%, P < .001). Venous thromboembolism was independently associated with greater odds of mortality (AOR:1.7 95% CI 1.6-1.9), increased costs (+27, 700 95% CI 23, 100-28, 300) and greater odds of 30-day readmissions (AOR 1.3 95% CI 1.2-1.4). Discussion: Despite national efforts to reduce its incidence, VTE affects nearly 1/100 EGS patients and is associated with increased odds of mortality as well as costs, and readmissions. Tailored approaches are warranted to reduce the impact of this pernicious complication.